Strategi SWOT dalam Melestarikan Kuliner Tradisional Sebagai Identitas Daerah Di Era Moderen - Yeri Resika; Moliza Gusriani (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Pempek is a traditional food originating from Palembang, South Sumatra, and has become an Indonesian culinary icon. This article analyzes pempek using a SWOT (Strengths, Weaknesses, Opportunities, Threats) approach to assess the potential and challenges in developing and preserving pempek as a cultural product and economic commodity. The method of this research used by descriptive qualitative from literature review and observation. The analysis shows that pempek possesses strengths in its unique flavor and high nutritional value, but still faces challenges such as dependence on certain fish ingredients. Opportunities are wide open through product innovation and digital marketing, although competition from the modern food market poses a significant threat.